Chronic Effects of Blast-Related TBI on Subcortical Functional Connectivity in Veterans. (6th June 2016) - Newsome, Mary R.; Mayer, Andrew R.; Lin, Xiaodi; Troyanskaya, Maya; Jackson, George R.; Scheibel, Randall S.; Walder, Annette; Sathiyaraj, Ajithraj; Wilde, Elisabeth A.; Mukhi, Shalini; Taylor, Brian A.; Levin, Harvey S.
Abstract: Objectives: Blast explosions are the most frequent mechanism of traumatic brain injury (TBI) in recent wars, but little is known about their long-term effects.Methods: Functional connectivity (FC) was measured in 17 veterans an average of 5.46 years after their most serious blast related TBI, and in 15 demographically similar veterans without TBI or blast exposure. Subcortical FC was measured in bilateral caudate, putamen, and globus pallidus. The default mode and fronto-parietal networks were also investigated.Results: In subcortical regions, between-groups t tests revealed altered FC from the right putamen and right globus pallidus. However, following analysis of covariance (ANCOVA) with age, depression (Center for Epidemiologic Studies Depression Scale), and posttraumatic stress disorder symptom (PTSD Checklist – Civilian version) measures, significant findings remained only for the right globus pallidus with anticorrelation in bilateral temporal occipital fusiform cortex, occipital fusiform gyrus, lingual gyrus, and cerebellum, as well as the right occipital pole. No group differences were found for the default mode network. Although reduced FC was found in the fronto-parietal network in the TBI group, between-group differences were nonsignificant after the ANCOVA.Conclusions: FC of the globus pallidus is altered years after exposure to blast related TBI. Future studies are necessary to explore the trajectory of changes in FC in subcortical regions after blast TBI, the effects of isolated versus repetitive blast-related TBI, and the relation to long-term outcomes in veterans. ( JINS, 2016, 22, 631–642)